COVID-19 Special Section Editorial. Shaping proactive higher education: Pandemic research and its value for future-proofing - Anca Greere (Universidad de Deusto, 2021)
This editorial to the Special Section on COVID-19 emphasises the importance of researching pandemic realities and the value that the findings can bring to the way we shape decisions in the future, for the 'new normal'. The pandemic, with its rapidly changing timeline, required swift action in untrialled circumstances and its consequences have been experienced differently by diverse institutions and across national contexts. Depending on the roles and responsibilities we may have taken on during this time, our capabilities to document our experiences and emerging trends have varied.